2019
DOI: 10.1186/s13071-019-3560-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and activity of ATP-binding protein in Bacillus thuringiensis toxicity modulation against Aedes aegypti

Abstract: Background Bacillus thuringiensi s israelensis (Bti) is a widely used mosquitocidal microbial pesticide due to its high toxicity. ATP-binding proteins (ABP) are prevalently detected in insects and are related to reaction against Bti toxins. However, the function of ABP in mosquito biocontrol is little known, especially in Aedes aegypti . Therefore, this study aimed to clarify the function of ABP in Ae. aegypti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another study suggested that Cry11Aa toxicity in Ae. aegypti also depends on an ATP-binding cassette protein [ 61 ], although more studies are necessary to determine the role of this molecule as a Cry toxin receptor in mosquitoes. The receptors characterized for the Cry4Ba toxin in Ae.…”
Section: Toxins and Mode Of Actionmentioning
confidence: 99%
“…Another study suggested that Cry11Aa toxicity in Ae. aegypti also depends on an ATP-binding cassette protein [ 61 ], although more studies are necessary to determine the role of this molecule as a Cry toxin receptor in mosquitoes. The receptors characterized for the Cry4Ba toxin in Ae.…”
Section: Toxins and Mode Of Actionmentioning
confidence: 99%
“…In A. aegypti , galectin-14 can compete with Cry11Aa by binding to the Cry receptor ALP1 [ 143 ]. Consistently, galectin-6 was found to interact with ALP1, thus affecting the toxicity of Cry proteins [ 144 ].…”
Section: Immunity Induced By Btmentioning
confidence: 96%
“…Respecto a la CL95, las concentraciones evaluadas aquí, fueron menores a las recientemente encontradas por Gómez-Vargas et al (2018), quienes determinaron la efectividad de tabletas de Bti serotipo H14, Bti-CECIF, producido en Colombia, hallando valores entre 0,40 a 0,93ppm.Lo anterior corrobora la viabilidad del uso de Bti en los programas de control vectorial de Colombia, donde se utilizan tres larvicidas: el Bti, el triflumurón (inhibidor de la síntesis de quitina en insectos) y el OP temephos (MinSalud et al 2011), donde la resistencia está ampliamente diseminada(Grisales et al 2013), lo que enfatiza, aún más, el uso del Bti. No obstante, los problemas inherentes al uso del Bti en campo, como tasa de ingestión, edad y densidad de las larvas, temperatura, radiación solar, entre otras, deben ser evaluados(Zhao et al 2019).…”
unclassified